Особливості гарантування речових прав на об’єкти нерухомого майна, які будуть споруджені в майбутньому у контексті діяльності нотаріусів - Кіріяк; Kiriiak, Оксана; Oksana (Київ: Алерта, 2023)
In the whole world, the role o f regional spatial planning as the most effective tool for the use o f the area is growing, in Ukraine there is also a need to formulate an appropriate policy in this area. This is undeniably important, because a properly constructed infrastructure network contributes to balanced socio-economic development o f regions, improvement o f people’s quality o f life, and also provides jor responsible management o f natural resources, protection o f the environment, and recovery after the victory over the aggressor. The category o f guaranteeing property rights to real estate objects that will be built in the future belongs to those legal phenomena o f civil law, the legislative regulation o f which is just beginning to acquire an orderly character, and in this the legislator has laid real prospects jor further development, and therefore for the next detailed study such rights. The Ukrainian state has gone a long way towards strengthening institutionalization and guaranteeing property rights to real estate objects that will be built in the future. The current situation in the researched area is characterized by the ratio o f the relatively consistent consolidation o f the main guarantees o f the realization o f property rights with the obviously unsatisfactory state o f their practical implementation, which is expressed in the impossibility for the majority o f the population to fully enjoy their rights, in their systematic violations and in the absence o f reliable mechanisms for their restoration and protection. The same with regard to further scientific research, we can confidently conclude that in the current conditions, the epicenter o f doctrinal and legal efforts should shift from the formal recognition and ascertainment o f real property rights to real estate objects that will be built in the future, to the implementation o f their real guarantee.
Keywords: notary, guarantee o f rights, real estate, objects o f unfinished construction, property rights, notarial authorization, notarial procedures, legislative amendments, legal relations, notarial process.